Comparative evaluation of virgin and recycled polypropylene fibre reinforced concrete. (1st July 2016) - Yin, Shi; Tuladhar, Rabin; Riella, Jacob; Chung, David; Collister, Tony; Combe, Mark; Sivakugan, Nagaratnam
Highlights: Reinforcement of recycled PP fibre in concrete footpaths and precast panels was studied. Post-cracking performance of fibre reinforced concrete was assessed by CMOD and RDPT. Recycled PP fibre has good alkali resistance in concrete and other alkaline environments. Recycled PP fibre shows comparable post-cracking reinforcement with virgin PP fibre. Abstract: Use of macro recycled plastic fibres in reinforcing concrete footpaths and precast panels offers significant economic and environmental benefits over traditionally used virgin plastic fibres or steel fibre and mesh. However, wide adoption of recycled plastic fibres by construction industries has not yet been seen due to limited data available on their durability, mechanical properties and performance in concrete. This paper reports findings from a laboratory study on the alkali resistance and performance of recycled polypropylene (PP) fibres in the 25 MPa and 40 MPa concretes, used for footpaths and precast panels, respectively. The recycled PP fibre was proven to have very good alkali resistance in the concrete and other alkaline environments. The recycled PP fibre showed excellent post-cracking performance in concrete, bringing in significant ductility. In the 40 MPa concrete the effectiveness of reinforcement of PP fibres depended on their Young's modulus and tensile strength in the crack mouth opening displacement (CMOD) test. Since the recycled PP fibre was found to have lower tensile strength but higher Young's modulus than those of virgin PP fibre, the recycled PP fibre produced similar or slightly lower reinforcement than that of virgin PP fibre. In the 25 MPa concrete, the Young's modulus of fibres was more effective on their reinforcement than the tensile strength, thus the recycled PP fibre produced better reinforcement than that of virgin PP fibre.